Acoustical Investigation of Adhesion in Liquid Metal–Ceramic Interfaces - Hadef, Zakaria; Doghmane, Abdellaziz; Kamli, Kenza (Металлофизика и новейшие технологии, 2018)
In this paper, we briefly review and analyse results of an acoustical investigation of adhesion in metal–ceramic interfaces based on the determination of the slope parameter, which is defined by the linear correlation between the work of adhesion of various liquid metal–ceramic systems and the sound propagation velocity of plate acoustical wave in the corresponding metals. The dependence of values of the work of adhesion slope parameter for several ceramic materials on the acoustic impedances of the corresponding ceramics is examined. The obtained results permit the interpretation of the wave propagation nature in these interfaces according to the existence and the excess of the interfacial bonding.